Story-takers : public pedagogy, transitional justice and italy's non-violent protest against ... the mafia. - Salvio, Paula (Toronto Italian studies., 2017)
"The Story-Takers charts new territory in public pedagogy through an exploration of the multiple forms of communal protests against the mafia in Sicily. Writing at the rich juncture of cultural, feminist, and psychoanalytic theories, Paula M. Salvio draws on visual and textual representations including shrines to those murdered by the mafia, photographs, and literary and cinematic narratives, to explore how trauma and mourning inspire solidarity and a quest for justice among educators, activists, artists, and journalists living and working in Italy. Salvio reveals how the anti-mafia movement is being brought out from behind the curtains, with educators leading the charge. She critically analyses six cases of communal acts of anti-mafia solidarity and argues that transitional justice requires radical approaches to pedagogy that are best informed by journalists, educators, and activists working to remember, not only victims of trauma, but those who resist trauma and violence."--